Approach of Image Processing in Diagnosis and Medication of Fungal Infections in Pet Animals (International Journal of Innovative Research in Computer Science & Technology, 2020)
The focus of this paper is to design and  develop the Artificial Intelligence and Machine Learning  based system which detects the fungal infection on a pet  animal (especially Dog and Cat), and provide the treatment  for it. It also provides the causes, Symptoms, Prevention for  it. The proposed system integrates on Machine Learning  algorithm trained on disease dataset, it first detects the  species of pet animal by capturing the image of fungal  infection of pet by using camera or by uploading the image  in the system from the file explorer, and then provide the  diagnosis about the fungal disease and its medication and  treatment also. Although our system will verify the scan  image for determining the diseases in canine. Diagnosing  the Fungal Infection on pet animal quickly and accurately  has the economic effectiveness.
Keywords: Disease Diagnosis Treatment Animal Pet Image Dataset Machine Learning Image processing